2011
DOI: 10.4314/ijbcs.v4i4.63045
|View full text |Cite
|
Sign up to set email alerts
|

Etude de la qualité bactériologique des aliments vendus sur le campus de l’Université d’Abomey Calavi au Bénin

Abstract: RESUMESelon l'Organisation Mondiale de la Santé, deux millions de personnes dans les pays en développement décèdent chaque année, à cause des intoxications alimentaires contractées en partie dans la restauration de masse. Le double objectif de cette étude était d'analyser la qualité bactériologique des aliments vendus en restauration rapide sur le campus universitaire et de déterminer la fréquence des bactéries multi résistantes (BMR) isolées. En six mois; 390 échantillons d'aliments ont été collectés et analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
5
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 20 publications
2
4
5
1
Order By: Relevance
“…Knowing that the presence of Salmonella, Staphylococci and ASR in drinks reflects their insalubrity, 8.88% of the samples are unsatisfactory and can be considered dangerous for consumption. These results are contrary to those of Mouloudi (34) who found no Salmonella and Staphylococci in food and lower than those of Ahoyo et al (14) who reported that 27% of food sampled in the University of Abomey-Calavi (Benin) was contaminated with Salmonella especially Salmonella enteritidis. The count of thermotolerant coliforms in beverages showed that 6.67% of samples are satisfactory, contrary to the percentage (16%) reported by Ahoyo et al (14) who detected 21 isolates of Escherichia coli O157 in similar foods in Benin.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Knowing that the presence of Salmonella, Staphylococci and ASR in drinks reflects their insalubrity, 8.88% of the samples are unsatisfactory and can be considered dangerous for consumption. These results are contrary to those of Mouloudi (34) who found no Salmonella and Staphylococci in food and lower than those of Ahoyo et al (14) who reported that 27% of food sampled in the University of Abomey-Calavi (Benin) was contaminated with Salmonella especially Salmonella enteritidis. The count of thermotolerant coliforms in beverages showed that 6.67% of samples are satisfactory, contrary to the percentage (16%) reported by Ahoyo et al (14) who detected 21 isolates of Escherichia coli O157 in similar foods in Benin.…”
Section: Discussioncontrasting
confidence: 96%
“…In our study, 21.42% of bacteria isolated from drinks developed resistance to more than three antibiotics from different families and constitute Multi-Resistant Bacteria (MRB). This percentage is lower than that (36%) obtained by Ahoyo et al (14) in Benin who isolated 325 strains of potentially pathogenic bacteria with 36% multi-resistant to antibiotics, including 44% broad spectrum beta-lactamase-producing Escherichia coli (ECBLSE), 32% methicillin-resistant Staphylococcus aureus and 24% vancomycin-resistant enterococci. BMRs are often isolated in hospitals with frequencies comprised between 12 and 28.7% as reported by Ahoyo et al (14) and are responsible for severe nosocomial infections.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…These foods analyzed are excessively loaded with Coagulase-positive staphylococci, it is sufficient proof of lack of personal hygiene. Our results are similar to other studies in the same direction (Mensah et al, 2002;Barro et al, 2002;Christison et al, 2007;Ahoyo et al, 2010;Sadık et al, 2014;Ashraf et al, 2014;Kassé et al, 2014;Ogunyemi et al, 2015;Soncy et al, 2015). These results could be explained by the fact that most of the food handlers do not use hair net, gloves and other protective gear when preparing and serving.…”
Section: Discussionsupporting
confidence: 92%
“…Olonitola et al (2007) à Zaria au Nigéria avaient prouvé le rôle des souches de E. coli et de Klebsiella pneumoniae dans les infections urinaires, bien entendu que partout dans le monde, la colonisation des urines devient un problème de santé publique majeur (Hailaji et al, 2016;Abreu et al, 2013). En dehors de la sphère périnéale, la sphère respiratoire serait également colonisée par ces souches BLSE (Jeny et Nabaraj, 2015;Olugbue et Onuoha, 2011) et même retrouvées dans les denrées alimentaires au Bénin suivant les travaux d 'Ahoyo et al (2010) jusqu'à 35% de E. coli BLSE.…”
Section: Introductionunclassified